Normal Limits in Relation to Age, Body Size and Gender of Two-Dimensional Echocardiographic Aortic Root Dimensions in Persons ≥15 Years of Age - Devereux, Richard B.; de Simone, Giovanni; Arnett, Donna K.; Best, Lyle G.; Boerwinkle, Eric; Howard, Barbara V.; Kitzman, Dalane; Lee, Elisa T.; Mosley, Thomas H.; Weder, Alan; Roman, Mary J. (The American journal of cardiology, 2012)
Nomograms to predict normal aortic root diameter for body surface area (BSA) in broad ranges of age have been widely used but are limited by lack of consideration of gender effects, jumps in upper limits of aortic diameter among age strata, and data from older teenagers. Sinus of Valsalva diameter was measured by American Society of Echocardiography convention in normal-weight, nonhypertensive, nondiabetic subjects ≥15 years old without aortic valve disease from clinical or population-based samples. Analyses of covariance and linear regression with assessment of residuals identified determinants and developed predictive models for normal aortic root diameter. In 1,207 apparently normal subjects ≥15 years old (54% women), aortic root diameter was 2.1 to 4.3 cm. Aortic root diameter was strongly related to BSA and height (r = 0.48 for the 2 comparisons), age (r = 0.36), and male gender (+2.7 mm adjusted for BSA and age, p <0.001 for all comparisons). Multivariable equations using age, gender, and BSA or height predicted aortic diameter strongly (R = 0.674 for the 2 comparisons, p <0.001) with minimal relation of residuals to age or body size: for BSA 2.423 + (age [years] × 0.009) + (BSA [square meters] × 0.461) − (gender [1 = man, 2 = woman] × 0.267), SEE 0.261 cm; for height 1.519 + (age [years] × 0.010) + (height [centimeters] × 0.010) − (gender [1 = man, 2 = woman] × 0.247), SEE 0.215 cm. In conclusion, aortic root diameter is larger in men and increases with body size and age. Regression models incorporating body size, age, and gender are applicable to adolescents and adults without limitations of previous nomograms.